2022
DOI: 10.3390/brainsci12101289
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Executive and Cognitive Functions in Children with Restless Sleep Disorder: A Pilot Study

Abstract: Restless sleep disorder affects children and is characterized by frequent nocturnal movements, iron deficiency, and daytime symptoms such as poor school performance or behavioral problems. Although sleep parameters have been thoroughly studied and daytime sleepiness has been previously assessed, neurocognitive and executive functions have not. In this study, we evaluated neurocognitive functions in a group of 13 children diagnosed with restless sleep disorder using the National Institute of Health Toolbox (NIH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…It has already been reported that, in healthy adult controls, these movements correlate positively with sleep stage N1 percentage, arousal index, sleep stage shifts, and negatively with sleep stage N3 [ 18 ]. It has also been reported that LMM, which characterizes a recently introduced pediatric sleep-related movement disorder called restless sleep disorder [ 35–37 ], might be frequent in children with RLS [ 38 ] and is associated with important clinical consequences, such as excessive daytime sleepiness and decreased quality of life [ 17 ], or cognitive functions, such as selective attention [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that, in healthy adult controls, these movements correlate positively with sleep stage N1 percentage, arousal index, sleep stage shifts, and negatively with sleep stage N3 [ 18 ]. It has also been reported that LMM, which characterizes a recently introduced pediatric sleep-related movement disorder called restless sleep disorder [ 35–37 ], might be frequent in children with RLS [ 38 ] and is associated with important clinical consequences, such as excessive daytime sleepiness and decreased quality of life [ 17 ], or cognitive functions, such as selective attention [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study is an important contribution to the literature to demonstrate a high prevalence of restless sleep disorder in children with sleep‐related epilepsy, associated with an increased number of LMM and frequent LMM‐associated nocturnal awakenings. It was recently shown that RSD affects neurocognitive and executive functions in children, resulting in poor school performance or behavioural problems (DelRosso, Vega‐Flores et al, 2022b). As restless sleep is highly prevalent in these children, they are often referred to a sleep centre to assess sleep disruption and to rule out nocturnal seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Más de la mitad de los autores (61,3%) sugieren que la incidencia de los trastornos del sueño difiere en función de los ámbitos de estudio en el contexto escolar: matemáticas y ciencias (15.4%) por ejemplo Brockmann et al (2015), Gatica et al (2017), etc., lenguaje (11.5%) por ejemplo Bennett et al (2018), Brockmann et al (2015, etc., y educación física (3.8%) por ejemplo Bennett et al (2018), Cladellas i Pros et al (2011, etc. Por otra parte los trastornos no respiratorios del sueño, disminuyen la atención (17.6%) por ejemplo Gómez y Genzel (2020), del Rosso et al (2022, etc., la memoria de trabajo así como la declarativa (11.8%), por ejemplo, Smith et al (2020), Williamson et al (2020), etc. En definitiva, sueño y rendimiento académico están relacionados; un sueño correcto tanto en calidad como en cantidad, así como unos hábitos del sueño adecuados que propicien su correcta higiene, conllevan mejora una mejora del rendimiento académico, reflejada tanto en los procesos cognitivos subyacentes como en las calificaciones. Al contrario, un sueño alterado influye en la disminución del rendimiento académico, así como en los procesos de aprendizaje.…”
Section: Afinidades Y Discrepancias Entre Los Documentos Analizadosunclassified